2016
DOI: 10.1007/s11242-016-0663-5
|View full text |Cite
|
Sign up to set email alerts
|

Volume-Based Modelling of Fault Reactivation in Porous Media Using a Visco-Elastic Proxy Model

Abstract: The injection of fluids into the subsurface takes place in the context of a variety of engineering applications such as geothermal power generation, disposal of wastewater, CO 2 storage and enhanced oil recovery. These technologies involve not only the underground emplacement of fluids in a geologic formation but also affect the stress state of these rocks. If the rock's strength is surpassed, these stress changes can even lead to failure. In this context, we present a conceptual approach to model fault reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 38 publications
(62 reference statements)
0
9
0
Order By: Relevance
“…The developed preconditioner exhibits good scalability properties for challenging problems regardless of dominant physics. Beck et al (2016) present a conceptual approach to model fault reactivation in porous media. They interpret failure as a dissipation of elastic energy and thus replace the originally linear elastic material law by a visco-elastic law.…”
Section: Research Area B: Numerical Methodsmentioning
confidence: 99%
“…The developed preconditioner exhibits good scalability properties for challenging problems regardless of dominant physics. Beck et al (2016) present a conceptual approach to model fault reactivation in porous media. They interpret failure as a dissipation of elastic energy and thus replace the originally linear elastic material law by a visco-elastic law.…”
Section: Research Area B: Numerical Methodsmentioning
confidence: 99%
“…The energies, into which the elastic energy is transformed, are not considered since they are either dissipated or negligible for the stress redistribution. There are other recently introduced approaches (Berge et al, 2017;Ucar et al, 2018;Gómez Castro et al, 2017) that calculate the stress drop required for reaching the equilibrium, which is in fact the excess shear stress. Our approach uses a constant value, and therefore ends up either beyond the equilibrium or does not yet reach it, the latter case would trigger immediately another failure event.…”
Section: Modelling Conceptmentioning
confidence: 99%
“…Poroelastic coupling plays a major role in the presence of faults and fractures (Rutqvist et al, ; Rutqvist & Stephansson, ; Segura & Carol, ). Faults are typically represented either as 3‐D failure zones with slip‐weakening rheology (Beck et al, ; Borja, ; Rutqvist et al, ), or as frictional contact surfaces (Ferronato et al, ; Ghassemi & Tao, ; Jha & Juanes, ; Morris, Hao, et al, ). The latter approach, adopted in this study, is consistent with the observed structure of mature faults, which suggests that shearing during earthquake slip events localizes within a thin granular core (Rice, ).…”
Section: Mathematical Model: Poroelasticity and Fault Frictional Behamentioning
confidence: 99%
“…Measures of tendency to slip, mobilized friction angle, Coulomb failure analysis (Reasenberg & Simpson, ), and estimates of coseismic fault slip based on simplified fault rheologies have proven very useful to understand the geomechanical challenges posed by subsurface energy technologies. Thermohydromechanical models of induced seismicity have focused on fault reactivation through estimates of tendency to slip (De Simone et al, ; Jacquey et al, ; Kim & Hosseini, ; Li & Laloui, ; Morris, Detwiler, et al, ; Rutqvist et al, ; Vidal‐Gilbert et al, ; Vilarrasa et al, ; Vilarrasa et al, ), estimates of coseismic slip from slip‐weakening friction laws (Beck et al, ; Cappa & Rutqvist, , ; Jeanne et al, ; Jha & Juanes, ; Morris, Hao, et al, ; Rinaldi et al, ; Rohmer, ; Taron & Elsworth, ), or connecting poroelastic stressing to models of earthquake production rate (Chang & Segall, , ; Dieterich, ; Segall & Lu, ). Over the past decade, there have been numerous contributions to hydromechanical modeling of induced seismicity, often combining two separate codes to sequentially solve for fluid flow and rock mechanics (Cappa & Rutqvist, , ; Jha & Juanes, ; Rutqvist et al, ).…”
Section: Introductionmentioning
confidence: 99%